Interpersonal Communication and Performance of Badminton Doubles Athletes in Jepara - Muhammad Ihsan Aulia Rahman; Limpad Nurrachmad (Universitas Negeri Semarang, 2026)
This study examines the role of interpersonal communication between badminton doubles partners in supporting the achievement of athletes from Jepara Regency. Interpersonal comm unication plays an important role in fostering cooperation, coordination, trust, and mutual understanding between partners during training- s, and competitive matches. The objectives of this study are to describe the forms of verbal and nonverbal interpersonal communication among badminton doubles athletes in Jepara Regency and to analyze the role of interpersonal communication in enhancing athletic performance and achievement. This research employed a qualitative method with a narrative design. Data were collected through observation, in-depth interviews, and documentation to gain comprehensive insights into the athletes’ experiences. The findings reveal that effective interpersonal communication significantly contributes to improving team cohesion, strategic coordination, self-confidence, and athletes’ ability to cope with competitive pressure. The study also found that openness, empathy, supportiveness, positivity, and equality are essential components in establishing harmonious relationships between partners. Conversely, miscommunication and a lack of openness may negatively affect performance during matches. Overall, effective interpersonal communication positively contributes to the achievement of badminton doubles athletes in Jepara Regency and supports the development of strong partnerships in pursuing common goals.